Photosynthate Regulation of the Root System Architecture Mediated by the Heterotrimeric G Protein Complex in Arabidopsis - Mudgil, Yashwanti; Karve, Abhijit; Teixeira, Paulo J. P. L.; Jiang, Kun; Tunc-Ozdemir, Meral; Jones, Alan M. (Frontiers in Plant Science, 2016)
Assimilate partitioning to the root system is a desirable developmental trait to control but little is known of the signaling pathway underlying partitioning. A null mutation in the gene encoding the Gβ subunit of the heterotrimeric G protein complex, a nexus for a variety of signaling pathways, confers altered sugar partitioning in roots. While fixed carbon rapidly reached the roots of wild type and agb1-2 mutant seedlings, agb1 roots had more of this fixed carbon in the form of glucose, fructose, and sucrose which manifested as a higher lateral root density. Upon glucose treatment, the agb1-2 mutant had abnormal gene expression in the root tip validated by transcriptome analysis. In addition, PIN2 membrane localization and level was altered in the agb1-2 mutant. The heterotrimeric G protein complex integrates photosynthesis-derived sugar signaling incorporating both membrane-and transcriptional-based mechanisms. The time constants for these signaling mechanisms are in the same range as photosynthate delivery to the root, raising the possibility that root cells are able to use changes in carbon fixation in real time to adjust growth behavior.